Drawing in the Land : Rock Art in the Upper Nepean, Sydney Basin, New South Wales - Dibden, Julie (ANU Press, 2019)
"Drawing in the Land offers an important contribution to the field of rock art research and Australian archaeology. It provides a detailed study of the previously under-examined rock art of the Hawkesbury/Nepean area of New South Wales. The study presents a detailed historiography of Australian rock art research and, through the lens of landscape archaeology, offers an innovative contribution to rock art studies in the wider Sydney Basin. The volume$1 (Bs theoretical focus on materiality, embodied practice and performance allows for the charting of ideational change and provides a unique contribution to the late Holocene archaeology of NSW and contact archaeology within Australia more broadly."s
English
Keywords: Australia; Art of indigenous peoples; Archaeology; archaeology; Australia; rock art; historiography